1997
DOI: 10.3109/02844319709085478
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Chitosan Complexes Stimulate Wound Healing in Human Skin

Abstract: The effect of heparin ionically linked to chitosan on the stimulation of re-epithelialisation of full thickness wounds in human skin was investigated in an in vitro model. After seven days of incubation, heparin-chitosan gel stimulated 9/10 of the full thickness wounds to re-epithelialise compared with only 3/10 of the wounds that were covered with chitosan gel or membrane, and none of the wounds incubated without gel or membrane or with heparin solution alone. Both dermal and epidermal cells were viable after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(73 citation statements)
references
References 26 publications
0
69
0
2
Order By: Relevance
“…Essa foi também a conclusão a que chegaram outros estudiosos, porém fazendo uso do material para outros fins. 1,19,22,23 Outro aspecto a ressaltar foi que não houve colonização do implante por células do hospedeiro, sendo esse um material que não possui poros, de superfície totalmente lisa. Dessa forma, inclusões de quitosana devem ser consideradas implantes que não sofrem integração com o hospedeiro, permanecendo com as características que apresentavam antes do contato com o receptor.…”
Section: Agradecimentounclassified
“…Essa foi também a conclusão a que chegaram outros estudiosos, porém fazendo uso do material para outros fins. 1,19,22,23 Outro aspecto a ressaltar foi que não houve colonização do implante por células do hospedeiro, sendo esse um material que não possui poros, de superfície totalmente lisa. Dessa forma, inclusões de quitosana devem ser consideradas implantes que não sofrem integração com o hospedeiro, permanecendo com as características que apresentavam antes do contato com o receptor.…”
Section: Agradecimentounclassified
“…Kratz et al prepared heparin-chitosan membranes and reported that the wound healing activity of heparin-chitosan complexes was dependent on heparin concentration. While 1.9% heparin was not sufficient to induce re-epithelialization, 7.7% of heparin included in the chitosan complexes led to almost complete re-epithelialization (Kratz et al, 1997). This suggests that, to reach therapeutic efficacy, a timely, controlled delivery of heparin at an appropriate dose is needed, which is achieved by ionic complexation with chitosan.…”
Section: Film Sponge and Powdermentioning
confidence: 99%
“…We have previously used this ionic interaction to microencapsulate primary hepatocytes [15,22]. Similar chitosan-GAG complexes have also been applied as aids to wound healing and tissue regeneration [23][24][25]. Membranes produced by the GAG-chitosan complex formation procedure appeared granular and textured under the phase contrast light microscope.…”
Section: Culture Membrane Formation and Morphologymentioning
confidence: 99%